Norway : Financial Sector Assessment Program-Technical Note-Risk Analysis and Stress Testing. (IMF Staff Country Reports; Country Report ;, 2020)
Much of the work of the FSAP was conducted prior to the COVID-19 outbreak. The risk and vulnerability analysis integrates the original work with a quantification of the impact of the COVID-19 crisis on bank solvency under two separate scenarios. The original 'market shock' scenario explores additional risks that feature less prominently in the COVID scenarios.